Proglacial zone dynamics revealed with high resolution UAV-based mapping in 2021 and 2023, Renard Glacier, Svalbard - Szałkowski, Adrian (Polish Polar Research, 2026)
Research on the dynamics of terrain relief changes in the foreland of Renard Glacier (Recherchefjorden, Spitsbergen) provide knowledge about geomorphological processes occurring in Bellsund, one of the biggest fjords in Svalbard archipelago. The aim of the study was to identify and characterize contemporary geomorphological transformations in the marginal zone of the glacier, resulting from intensive ice melting, with particular emphasis on the dynamics of changes within the tidal flat. Research material was obtained in 2021 and 2023 using an unmanned aerial vehicle (UAV). Advanced photogrammetric techniques were applied, including Agisoft Metashape Pro software, to develop a Digital Elevation Model and orthophotomap with exceptionally high resolution of 0.1 m/px. In addition, the mean annual retreat rate of glacier was estimated at 11.17 m yr⁻¹. The obtained data enabled terrain analysis with unprecedented detail, allowing for precise mapping of changes occurring over short time intervals. The greatest transformations were identified in the active zone at the glacier terminus, where melting ice generates significant amounts of water, intensifying transport processes and redeposition of material to further parts of the fluvial fan.